Contribution of Fe3O4 nanoparticles to the fouling of ultrafiltration with coagulation pre-treatment - Yu,W; Xu,L; Graham,N; Qu,J (Scientific Reports, 2015)
A coagulation (FeCl3)-ultrafiltration process was used to treat two different raw waters with/without the presence of Fe3O4 nanoparticle contaminants. The existence of Fe3O4 nanoparticles in the raw water was found to increase both irreversible and reversible membrane fouling. The trans-membrane pressure (TMP) increase was similar in the early stages of the membrane runs for both raw waters, while it increased rapidly after about 15 days in the raw water with Fe3O4 nanoparticles, suggesting the involvement of biological effects. Enhanced microbial activity with the presence of Fe3O4 nanoparticles was evident from the measured concentrations of extracellular polymeric substances (EPS) and deoxyribonucleic acid (DNA), and fluorescence intensities. It is speculated that Fe3O4 nanoparticles accumulated in the cake layer and increased bacterial growth. Associated with the bacterial growth is the production of EPS which enhances the bonding with, and between, the coagulant flocs; EPS together with smaller sizes of the nano-scale primary particles of the Fe3O4-CUF cake layer, led to the formation of a lower porosity, more resilient cake layer and membrane pore blockage.